2015
DOI: 10.1007/s10453-015-9391-5
|View full text |Cite
|
Sign up to set email alerts
|

Site-related and seasonal variation of bioaerosol emission in an indoor wastewater treatment station: level, characteristics of particle size, and microbial structure

Abstract: The emission of the airborne bacteria and fungi from an indoor wastewater treatment station adopting an integrated oxidation ditch with a vertical circle was investigated. Microbial samples were collected by the six-stage viable Andersen cascade impactor, and the samples were collected in triplicate in each sampling site per season. Culture-based method was applied to determine the concentrations of the airborne bacteria and fungi, while the cloning/ sequencing method was used to characterize the genetic struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 45 publications
1
8
0
2
Order By: Relevance
“…In contrast to bacteria, the highest fungal concentration was recorded in the dry season than wet season and this corresponds to the results of other researchers [9,39]. In previous studies, the highest concentration of bioaerosol was found in the air samples of wastewater treatment facilities during summer and autumn seasons than that of spring and winter seasons because of small rainfall and suitable temperature [40,41].…”
Section: Resultssupporting
confidence: 89%
“…In contrast to bacteria, the highest fungal concentration was recorded in the dry season than wet season and this corresponds to the results of other researchers [9,39]. In previous studies, the highest concentration of bioaerosol was found in the air samples of wastewater treatment facilities during summer and autumn seasons than that of spring and winter seasons because of small rainfall and suitable temperature [40,41].…”
Section: Resultssupporting
confidence: 89%
“…Most previous studies on particle size distribution have focused on microbes derived from buildings, oceans and open biomass burning ( Deacon et al, 2009 ; Lazaridis et al, 2015 ; Katsivela et al, 2017 ; Li et al, 2017 ; Wei et al, 2019 ); however, scarce information is available about the aerospore size distribution of plant fungal pathogens. In our research, the particle size of C. cassiicola released by cucumber plants ranged predominately from 2.1 to 4.7 μm (accounting for 71.97%), which was different from the particle size of most culturable mold fungi distributed in the 1.1–3.3 μm size range ( Deacon et al, 2009 ; Ding et al, 2016 ), possibly because the average dimension of C. cassiicola (82.34 μm × 7.11 μm) is much larger than the average dimension of most mold fungi (3.78 μm × 3.50 μm) (unpublished data). The current lack of information on the particle size distribution of pathogens emitted from crop plants limits further study to model dispersion ( Taha et al, 2007 ).…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have suggested that the structure, size, concentration, and microbial population of bioaerosols is affected by the source of production, the mechanism of air diffusion, and in general, the weather conditions, such as temperature, humidity, wind speed, and UV index (12)(13)(14). (41). In this study, the results demonstrated that among the selected units, the highest concentrations of fungi were observed in the grit chamber unit.…”
Section: Discussionmentioning
confidence: 60%